Effects of ultrasound in coating nano-precipitated CaCO3 with stearic acid - Kow, Kien Woh; Abdullah, Ezzat Chan; Abdul Raman, Abdul Aziz (Wiley, 2009)
Nano-Precipitated CaCO3 (NPCC) are coated with stearic acid to improve its dispersion in polymer as well as to reduce agglomeration. In this work, coating was done by wet method using ethanol. Ultrasonication was applied to NPCC to de-agglomerate micron size NPCC into smaller size. Effects of amplitude, temperature and energy input of ultrasonication was investigated. The amplitude was varied from 60 to 100 whereas temperature was varied from 5 degrees C to 45 degrees C. The energy input was stressed up from 3.6 kJ to 180 kJ. Mean diameter of NPCC were observed by using Particle Size Analyzer and Transmission Electron Microscopy (TEM). It was found that mean diameter of NPCC do not vary significantly with temperature. Mean diameter of NPCC, however, decreases exponentially with the energy input. Comparisons were done on NPCC coated with others methods such as dry ball milling and aqueous coating TEM images show that coating NPCC with ultrasonication is more uniform than other methods. In addition, first derivative mass loss with temperature (DTG) reveals that NPCC coated with Ultrasonication do not contain excessive free acid as exhibited by those coated in aqueous and dry ball milling. (c) 2009 Curtin University of Technology and John Wiley & Sons, Ltd.